Towards an Ethical Approach of the Pharmacological Structure of Social Relations - Lolas Stepke, Fernando (2018)
In this study, the author analyzes a series of considerations regarding the ethical aspects of using psychoactive substances, which he classifies into three types: medical or therapeutic, recreational, and performance-enhancing. He also discusses the problems around self-administration and administration by others of such substances. Psychoactive substances have given rise to long and thorough researches, assays and uses, in which economic factors play an important role, and have modified our knowledge of human nature. Therefore, it is urgent to discuss the ethical and legal aspects of their future use.